Epidemiology and risk factors of equine parvovirus-hepatitis, hepacivirus, Pegivirus caballi, and Pegivirus equi in horses from the Southern United States - Subarna Barua; Asfiha Tarannum; Laura Huber; Leslie A. Easterwood; Binu Velayudhan; Bibiana Petri Da Silveira; Ben Enyetornye; Noah D. Cohen; Kiril M. Dimitrov; Erika R. Schwarz; Alex Awtrey; Erin Groover; et al. (Veterinary Microbiology, 2026)

Decentralized energy in flexible energy system: Life cycle environmental impacts in Belgium - Dominik Huber; Daniele Costa; Alex Felice; Pieter Valkering; Thierry Coosemans; Maarten Messagie (Science of The Total Environment, 2023)

A wide range of protective and predisposing variants in aggrecan influence the susceptibility for otosclerosis - Allan Thomas Højland; Lisse J. M. Tavernier; Isabelle Schrauwen; Manou Sommen; Vedat Topsakal; Isabelle Schatteman; Ingeborg Dhooge; Alex Huber; Diego Zanetti; Henricus P. M. Kunst; Alexander Hoischen; Michael B. Petersen; et al. (Human Genetics, 2022)

Platelet concentrate as an additive to bone allografts: a laboratory study using an uniaxial compression test - David Putzer; Markus Dobersberger; Alex Pizzini; Debora Coraça-Huber; Christoph Ammann; Michael Nogler (Cell and Tissue Banking, 2018)

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

Genetic variants in the RELN gene are associated with otosclerosis in multiple European populations - Isabelle Schrauwen; Megan Ealy; Erik Fransen; Kathleen Vanderstraeten; Melissa Thys; Nicole C. Meyer; Marcel Cosgarea; Alex Huber; Manuela Mazzoli; Markus Pfister; Richard J. H. Smith; Guy Van Camp (Human Genetics, 2010)